Pengembangan Multimedia Pembelajaran Interaktif Berbasis Platform Genially pada Materi Perangkat Keras Komputer (Hardware) Pelajaran Informatika di Kelas VII SMPN 3 Kuningan - Firjatullah, Rizal; Fitriah Nurjanah, Hifni (Indo-MathEdu Intellectuals Journal, 2025)
This study aimed to design and develop interactive learning multimedia utilizing the Genially platform to support the teaching of hardware concepts for seventh-grade junior high school students. The research adopted a Research and Development (R&D) approach, employing the Alessi and Trollip model, which encompasses the planning, design, and development phases. Participants included subject matter experts, media experts, and 30 students from SMPN 3 Kuningan. Data were gathered through observations, interviews, questionnaires, and pretest–posttest assessments, and analyzed using descriptive statistics, percentage scores, and Likert-scale evaluations. Validation results demonstrated a high level of feasibility (84%), with positive learner responses of 75.25% in the small-group trial and 87% in the large-group trial. Furthermore, posttest scores showed a statistically significant improvement compared to pretest scores. These findings indicate that the Genially-based multimedia is both pedagogically feasible and effective in enhancing students’ comprehension of hardware-related content.